Féminismes - Babin, Sylvette; Griffiths, Jennifer; Behiery, Valerie; Buurman, Nanne; St-Gelais, Thérèse; Dubois, Anne-Marie; Toulouse (Esse arts + avis, 2017)
Ce numéro s’intéresse aux rapports singuliers entre l’art et les féminismes. En tenant compte de la multiplicité des subjectivités et de l’hétérogénéité des femmes, il s’agit de faire connaitre comment les multiples pratiques et les théories sur l’art participent à déconstruire les oppressions et les limites liées au genre. On présente une sélection de pratiques féminines et féministes, militantes ou non, issues d’approches et de communautés diverses. Les différentes revendications, prises de position et affirmations témoignent de la diversité des artistes : subversion, soulèvement protestataire, remise en question des archétypes de genre et d’hétéronormativité, approche féministe postcoloniale, résurgence des pratiques ancestrales, représentation de soi, utilisation consciente et assumée de la séduction sont autant de manières de dire, encore, la nécessité des féminismes.
Keywords: approches et analyses; art contemporain; artistes féministes; arts; arts visuels et médiatiques; corps; cours; discipline; femmes* artistes; féminisme autochtone; féminisme décolonial; féminisme islamique; har4600; histoire de l'art; intersectionnalité; premier cycle; thématiques

In the name of women's rights: the rise of femonationalism - Farris, Sara R. (Duke University Press, 2017)
Sara R. Farris examines the demands for women's rights from an unlikely collection of right-wing nationalist political parties, neoliberals, and some feminist theorists and policy makers. Focusing on contemporary France, Italy, and the Netherlands, Farris labels this exploitation and co-optation of feminist themes by anti-Islam and xenophobic campaigns as “femonationalism.” She shows that by characterizing Muslim males as dangerous to western societies and as oppressors of women, and by emphasizing the need to rescue Muslim and migrant women, these groups use gender equality to justify their racist rhetoric and policies. This practice also serves an economic function. Farris analyzes how neoliberal civic integration policies and feminist groups funnel Muslim and non-western migrant women into the segregating domestic and caregiving industries, all the while claiming to promote their emancipation. In the Name of Women's Rights documents the links between racism, feminism, and the ways in which non-western women are instrumentalized for a variety of political and economic purposes.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; approches et analyses; cours; discipline; europe; france; féminisme islamique; fémonationalisme; histoire et politique; intersectionnalité; italie; justice sociale; pays-bas; pol4212; premier cycle; périodes historiques; racisme; régions géographiques; science politique; science politique et droit; sciences humaines; sociologie; systèmes d'oppressions; thématiques

Islamicate Sexualities: The Artworks of Ebrin Bagheri - Gayed, Andrew (esse arts + opinions, 2017)
As a push against colonial forces and imperialism, homosexuality in the Middle East was historically made into an illegal identity category—one that, many argue, did not exist prior to increased contact with Western explorers and travellers. It is important to understand how the emergence of the Gay International coincided with that of Western gay sexuality studies. These issues are all at the forefront in the study of Islamicate sexualities. “Islamicate,” as defined by Marshal Hodgson, refers not directly,to the religion of Islam itself, but to the social and cultural complexities historically associated with Islam, including non-Muslims living within the same regions. Only by keeping imperialism at the forefront of the study of sexualities can we better situate how pre-modern Islamicate sexual scripts have resisted complete colonization and continue to exist in the diaspora.
Keywords: LGBTQIA2+; amériques; approches et analyses; arts; asie; canada; cours; discipline; féminisme islamique; har4600; histoire de l'art; iran; premier cycle; queer; ressource en ligne; régions géographiques; thématiques